2017
DOI: 10.3168/jds.2016-11506
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of 10 calving and fertility traits in Holstein dairy cattle with special regard to chromosome 18

Abstract: Over the last decades, a dramatic decrease in reproductive performance has been observed in Holstein cattle and fertility problems have become the most common reason for a cow to leave the herd. The premature removal of animals with high breeding values results in both economic and breeding losses. For efficient future Holstein breeding, the identification of loci associated with low fertility is of major interest and thus constitutes the aim of this study. To reach this aim, a genome-wide combined linkage dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 57 publications
5
37
0
Order By: Relevance
“…Although this QTL has been detected by several studies, the causative gene or mutation is still missing. A few candidate genes are located in this QTL region, including clusters of sialic acid binding Ig-like lectin genes and zinc finger protein genes; however, several studies have failed to conclusively identify the causal genetic variant (Cole et al, 2009;Seidenspinner et al, 2009;Purfield et al, 2015;Mao et al, 2016;Müller et al, 2017). Future studies are still needed to pinpoint the candidate genes and mutations underlying this large QTL on fertility.…”
Section: Major Fertility Qtl On Bta18mentioning
confidence: 99%
“…Although this QTL has been detected by several studies, the causative gene or mutation is still missing. A few candidate genes are located in this QTL region, including clusters of sialic acid binding Ig-like lectin genes and zinc finger protein genes; however, several studies have failed to conclusively identify the causal genetic variant (Cole et al, 2009;Seidenspinner et al, 2009;Purfield et al, 2015;Mao et al, 2016;Müller et al, 2017). Future studies are still needed to pinpoint the candidate genes and mutations underlying this large QTL on fertility.…”
Section: Major Fertility Qtl On Bta18mentioning
confidence: 99%
“…Genetic selection offers a sustainable tool to improve dairy cattle farming via the selection of animals with reduced susceptibility toward diseases, which in turn results in improved periparturient health. Until now, association and linkage studies have revealed promising results concerning bovine chromosome 18 (BTA18) and performance traits (Mao et al, 2016;Abo-Ismail et al, 2017;Müller et al, 2017;Wu et al, 2017). Concerning udder health, Kühn et al (2008) showed that the prediction of half-sib heifers with a high or low SCS was possible through marker-assisted selection regarding a confirmed QTL for SCS in the telomeric region of BTA18.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of genomic data, such as SNP markers and whole-genome sequence, have provided additional opportunities to improve dairy cattle fertility. Several studies identified SNP and deleterious haplotypes related to fertility and reproduction traits Nayeri et al, 2016;Parker-Gaddis et al, 2016;Müller et al, 2017). The inclusion of genomic information, such as SNP markers and variants from whole-genome sequence data, has provided better reliability estimates for fertility traits (Wiggans et al, 2011;Ortega et al, 2016;VanRaden et al, 2017).…”
mentioning
confidence: 99%